Correspondence on "K2Sb(P2O7)F: Cairo Pentagonal Layer with Bifunctional Genes Reveal Optical Performance". (8th December 2020) - Krivovichev, Sergey V.; Bindi, Luca
Abstract: Compounds with the fresnoite structure type possess remarkable chemical diversity and a range of unique physical properties, including nonlinear optical (NLO) activity. K2 Sb(P2 O7 )F, which was reported recently, belongs to this group and its structure is not novel in terms of either the topology or local coordination geometry around the Sb 3+ cations. The crystallographic disorder observed in the fresnoite‐type structures can be explained by twinning, which is frequent for non‐centrosymmetric crystals. Abstract : It is argued by Krivovichev and Bindi that the previously reported K2 Sb(P2 O7 )F has a fresnoite structure type that is not novel in terms of either the topology or local coordination geometry around the Sb 3+ ions. They argue that the crystallographic disorder observed in fresnoite‐type structures can be explained by twinning, which is frequent for non‐centrosymmetric crystals.